2009
DOI: 10.1111/j.1467-6494.2008.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Temporal Macrostructure of Life Narratives Across Adolescence: Beginnings, Linear Narrative Form, and Endings

Abstract: The ontogeny of the ability to describe people culminates in adolescence in the development of the life story. An overarching temporal macrostructure and framing by a prehistory and a future-oriented global evaluation of life helps integrate disparate autobiographical memories into a coherent story. Two life narratives each of 8-, 12-, 16-, and 20-year-olds (N=102) were analyzed in terms of how well-formed their beginnings and endings are and how much they follow a linear temporal order. By age 12, the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 55 publications
1
75
0
4
Order By: Relevance
“…Bohn, 2011]. There was also a tendency for the acquisition of the life script to correlate with the elaboration of beginnings and endings of life narratives [Bohn & Berntsen, 2008Habermas et al, 2009]. Although one study found that the acquisition of the life script was achieved by age 16 and did not increase after that, it is not clear when the life script begins to be acquired.…”
Section: Development Of Global Coherence Of the Life Storymentioning
confidence: 84%
See 1 more Smart Citation
“…Bohn, 2011]. There was also a tendency for the acquisition of the life script to correlate with the elaboration of beginnings and endings of life narratives [Bohn & Berntsen, 2008Habermas et al, 2009]. Although one study found that the acquisition of the life script was achieved by age 16 and did not increase after that, it is not clear when the life script begins to be acquired.…”
Section: Development Of Global Coherence Of the Life Storymentioning
confidence: 84%
“…Short entire life narratives have been collected orally in two developmental German samples with ages 12, 15, and 18 [Habermas & Paha, 2001] and with ages 8, 12, 16, and 20 at the beginning of an eight-year longitudinal study [for cross-sectional evidence, cf. Habermas & de Silveira, 2008;Habermas, Diel, & Welzer, 2013;Habermas, Ehlert-Lerche, & de Silveira, 2009; for the longitudinal confirmation, cf. Köber et al, 2015].…”
Section: Development Of Global Coherence Of the Life Storymentioning
confidence: 99%
“…Whereas the three types of linguistic coherence can be measured within a life narrative (Habermas & de Silveira, 2008;Habermas & Paha, 2001), only some aspects of the cultural concept of biography can be measured, for example, by looking at the development of beginnings and endings of life stories (Habermas, Ehlert-Lerche, & de Silveira, 2009). A more direct way to measure those aspects of the cultural concept of biography concerned with the temporal order of major life events is the cultural life script, introduced by Rubin (2002, 2004;Rubin & Berntsen, 2003).…”
Section: Life Story Coherencementioning
confidence: 99%
“…O aspecto temporal é atualmente investigado mais acuradamente por Fivush (2008), Habermas, Ehlert-Lerche e de Silveira (2009) e McAdams (2001. Estes modelos enfatizam a tendência integrativa da identidade narrativa.…”
Section: Conclusãounclassified